PROGRAM MODIFIKASI PROPORTIONAL GATE 431-PG2 MENJADI BACKUP KILN FEED PADA PT SOLUSI BANGUN INDONESIA - NOVALDY, RAMSYAH; Basuki (Rekayasa Sistem Energi dan Manufaktur (ReSEM), 2025)
The Kiln Feed System is a main system in clinker production. This system functions to weigh and convey Kiln Feed materials from the Blending silo (391-3S1) to the Preheater for the initial burning process. At PT Solusi Bangun Indonesia, the Kiln Feed System utilizes Pfister Feeder equipment (431-PF1). However, this machine frequently experiences failures, posing a risk of production losses in clinker manufacturing. According to data extracted from the Technical Information System (TIS), over the past 5 years, the kiln at PT Solusi Bangun Indonesia's Tuban plant has stopped 13 times, with each stop lasting an average of 90.47 hours. To address this issue, it has develop a new system that can serve as a backup Kiln Feed. This would involve designing a modification program for the Proportional Gate 431-PG2 to act as a backup Kiln Feed. This modification aims to prevent kiln shutdowns due to failures in the Pfister Feeder, which serves as the primary material feeding system for Kiln Feed at PT Solusi Bangun Indonesia Tbk.